Application of hazard analysis and critical control points technique in a cassava flour processing unit - Campos, Gevair; Xavier, Sueli Pereira (Brazilian Journal of Production Engineering, 2024)
This work applies the Hazard Analysis and Critical Control Points (HACCP) technique in a cassava flour processing unit in the municipality of Bonfinópolis de Minas-MG, identifying and proposing solutions for the main critical points to improve the safety and quality of the final product. A case study was conducted in a flour house located in the rural area of the municipality, mapping the production process to identify CCPs. The analysis of the CCPs, aiming to transform them into control points (CP), was carried out through the adoption of corrective measures. The resulting evidence identified non-conformities that could compromise the quality of the final product, such as lack of root integrity, inconsistent texture, and variations in the pulp color.